Meta‐analyses of habitat selection by fishers at resting sites in the pacific coastal region. Issue 5 (26th June 2013) - Aubry, Keith B.; Raley, Catherine M.; Buskirk, Steven W.; Zielinski, William J.; Schwartz, Michael K.; Golightly, Richard T.; Purcell, Kathryn L.; Weir, Richard D.; Yaeger, J. Scott
Abstract The fisher (Pekania pennanti) is a species of conservation concern throughout the Pacific coastal region in North America. A number of radiotelemetry studies of habitat selection by fishers at resting sites have been conducted in this region, but the applicability of observed patterns beyond the boundaries of each study area is unknown. Broadly applicable information on habitat selection by fishers in this region would be useful for conservation planning and for informing forest management decisions in areas where intensive field studies have not been conducted. To provide such information, we conducted formal meta‐analyses of habitat selection by fishers at resting sites in 8 study areas located from central British Columbia to the southern Sierra Nevada in California, including all areas that currently contain established fisher populations. Each study included in the meta‐analyses measured environmental attributes at sites used by fishers for resting (i.e., the immediate vicinity of resting structures; typically ≤0.5 ha) and at random or systematically located sites representing resource availability in each study area. We selected 9 environmental attributes that we expected to be associated with fisher resting sites: slope, heat load index, percent cover of vegetation ≥2 m above the ground, volume of moderately decayed logs ≥26 cm in mean diameter, basal area of live conifers 51–100 cm in diameter at breast height (dbh), basal area of live hardwoods 51–100 cm in dbh, basal area of moderately decayed snags 51–100 cm in dbh, mean dbh of live conifers ≥10 cm in dbh, and mean dbh of live hardwoods ≥10 cm in dbh. Despite substantial variation in environmental conditions among study locations, our analyses revealed statistically significant summary effect sizes for each of the 9 environmental attributes we analyzed. Fishers selected sites for resting that had steeper slopes, cooler microclimates, denser overhead cover, a greater volume of logs, and a greater prevalence of large trees and snags than were generally available. Thus, in areas within the Pacific coastal region where fishers have not been studied and data on selection of resting sites are lacking, our findings provide empirical support for management or conservation actions for fishers that promote the retention or development of these environmental attributes. © 2013 The Wildlife Society.